SOCIAL MEDIA DYNAMICS, PEER INFLUENCE, AND DATING BEHAVIOR AMONG ADOLESCENTS - Suci Fitriana Pramudya Wardani; Ayu Aminatussyadiah; Amrina Nur Rohmah (Siklus : Journal Research Midwifery Politeknik Tegal, 2026)
Adolescent dating behavior is influenced by various factors, including social media use and peer influence. Increased exposure to social media and peer interactions may affect adolescents’ dating behavior. This study aimed to determine the relationship between social media use, peer influence, and dating behavior among adolescents in one of the health vocational schools in Brebes Regency. This study used a descriptive correlational design with a cross-sectional approach. A total of 70 respondents were selected using total sampling. Data were collected using questionnaires and analyzed with the Chi-Square test. The results showed that 52 respondents (74.3%) had negative social media influence, 49 respondents (70.0%) had negative peer influence, and 38 respondents (54.3%) had good dating behavior. Bivariate analysis indicated no significant relationship between social media use and dating behavior (p-value = 0.242), and no significant relationship between peer influence and dating behavior (p-value = 0.283). The study concluded that social media use and peer influence were not significantly associated with adolescent dating behavior. Other factors such as self-control, parenting patterns, and reproductive health education may play a greater role.